School feeding contributes to micronutrient adequacy of Ghanaian schoolchildren. Issue 6 (28th September 2014) - Abizari, Abdul-Razak; Buxton, Christiana; Kwara, Lugutuah; Mensah-Homiah, Joseph; Armar-Klemesu, Margaret; Brouwer, Inge D.
<x content-type="archive" xml:space="preserve">Abstract</x> Without gains in nutritional outcomes, it is unlikely that school feeding programmes (SFP) could improve cognition and academic performance of schoolchildren despite the improvements in school enrolment. We compared the nutrient intake adequacy and Fe and nutritional status of SFP and non-SFP participants in a cross-sectional survey involving 383 schoolchildren (aged 5–13 years). Quantitative 24 h recalls and weighed food records, repeated in 20 % subsample, were used to estimate energy and nutrient intakes adjusted for day-to-day variations. The probability of adequacy (PA) was calculated for selected micronutrients and the mean of all PA (MPA) was calculated. The concentrations of Hb, serum ferritin, and soluble transferrin receptor (sTfR) and anthropometric measurements were used to determine Fe and nutritional status. Energy and nutrient intakes and their adequacies were significantly higher among SFP participants (P< 0·001). The MPA of micronutrients was significantly higher among SFP participants (0·61 v. 0·18; P< 0·001), and the multiple-micronutrient-fortified corn soya blend was a key contributor to micronutrient adequacy. In SFP participants, 6 g/l higher Hb concentrations (P< 0·001) and about 10 % points lower anaemia prevalence (P= 0·06) were observed. The concentration of sTfR was significantly lower among SFP participants (11·2 v. 124 mg/l; P= 0·04); however, there was no difference in the prevalence of Fe deficiency and Fe-deficiency anaemia between SFP and non-SFP participants. There was also no significant difference in the prevalence of thinness, underweight and stunting. In conclusion, the present results indicate that school feeding is associated with higher intakes and adequacies of energy and nutrients, but not with the prevalence of Fe and nutritional status indicators. The results also indicate an important role for micronutrient-dense foods in the achievement of micronutrient adequacy within SFP.